Family influences on talent development in sport - Knight, C. J. (Routledge handbook of talent identification and development in sport, 2017)
The purpose of this chapter is to unpack the role of the family in the development of talented athletes, focusing on how the family can support or detract from this process. When considering the role of the family in talent development, it is important to note that the majority of literature has focused upon parents` influence rather than considering the influence of siblings or extended family (Horn & Horn, 2007; Partridge, Brustad, & Babkes Stellino, 2008). As such, the majority of this chapter will focus upon parents` involvement. The chapter will start with an overview of the positive and negative influences of parents in sport. Next, a detailed examination of the role of the family throughout the process of athletic development will be provided and the consequences of supporting a talented athlete will be discussed. The chapter will then conclude with suggestions for future research for exploring the complexity of family influence within talent development.